Histochemical Study of Nissl Substance and Astrocytes in a Pentylenetetrazole-Induced Model of Epilepsy Treated with Musa Paradisiaca Stem Juice (Nigerian Journal of Physiological Sciences, 2025)
Epilepsy disrupts the transmission of electrical signals within the brain and is characterized by an enduring predisposition to generate epileptic seizures, with an average epidiemologic index of 60 million affected individuals worldwide. The study examined the neurohistochemistry of Nissl substance and astrocytes in epileptic rats administered Musa paradisiaca (MP) stem juice. Sixty minutes after the administration of escalating doses of MP stem juice and diazepam (an anticonvulsant), a seizure was induced using Pentylenetetrazole (PTZ). The animals were arbitrarily distributed into the groups A, B, C, D, and E. All of the animals were fed rat pellets and purified water. Group A served as the standard control, receiving rat pellets and deionized water. The animals in Group B, which served as the PTZ control, received intraperitoneal administration of 65mg/kg body weight of PTZ. Group C was the PTZ + Diazepam (DZP) treatment group, and the animals were given 4 mg/kg body weight of DZP orally 60 minutes prior to intraperitoneal administration of PTZ. Group D was given 2500 mg/kg body weight of MP stem juice orally for seven days prior to intraperitoneal administration of Pentylenetetrazole, followed by an hour of MP stem juice treatment [Low dose] Group E (PTZ + MP [High dose]) received 5000mg/kg body weight of MP stem juice orally for 7 days prior to intraperitoneal PTZ administration, followed by 1 hour of MP stem juice [High dose] post-treatment. On the histochemical components of tissue sections, MP stem juice (2500mg/kg and 5000mg/kg) and the DZP group of animals exhibited significant antiepileptic effects. Histochemical studies revealed that the intensity of staining of Nissl substances in Group B decreased in comparison to the treated groups (C, D, and E). Immunohistochemistry analysis of astrocytes revealed that DZP and MP treated groups (D and E) had fewer astrocyte expressions than the PTZ control group, which was densely populated with astrocytes. The findings indicate that administration of MP stem juice is beneficial for the local management of epilepsy and can also mitigate the neuronal damage associated with epileptic seizures to some extent.